An autumn biodiversity survey on heterotrophic and mixotrophic protists along a coast-to-offshore transect in the Gulf of Naples (Italy) - Gabriele Del Gaizo; Luca Russo; Maria Abagnale; Angela Buondonno; Marta Furia; Simona Saviano; Mauro Vargiu; Fabio Conversano; Francesca Margiotta; Maria Saggiomo; Isabella Percopo; Domenico D'Alelio (Advances in Oceanography and Limnology)
Plankton communities include both unicellular and multicellular organisms. An important unicellular component is represented by those protists (i.e., unicellular eukaryotes) that consume bacteria, other protists, and even small animals. These organisms are an important link between primary producers and metazoans, and they can also be ‘mixotrophic’, coupling phagotrophic and photoautotrophic behaviours. In this note, we report on the diversity of heterotrophic protists, or protozoo-plankton (from ‘protozoan plankton’), and mixotrophic protists, or mixo-plankton , which were sampled at two sites (coastal and offshore stations), at two depths (0 and 10 m), in the Gulf of Naples during the early autumn of 2020. Our survey identified dinoflagellates and oligotrich ciliates as the most abundant groups, while tintinnids (choreotrich ciliates) were less quantitatively relevant. The taxonomic composition in samples investigated herein remarked that reported by previous studies, except for the tintinnid Ascampbeliella armilla. A coast-to-offshore differentiation in the taxonomical composition of heterotrophic and mixotrophic protists was also observed, with some species more abundant within coastal waters and other better thriving in offshore ones. These differences were associated with distinct environmental and trophic conditions.